Antibacterial effect of Peronema canescens jack on the Staphylococcus aureus on the surface of acrylic resin - Fadriyanti, Okmes; Rahmad, Yulia; Gemilang, Muhammad Alif (Dentistry Faculty, 2024)
Background: Removable dentures made from Polymethyl Methacrylate (PMMA) are porous and can absorb saliva, leading to the attachment of microorganisms, including Staphylococcus aureus, which can trigger denture stomatitis. Preventing this condition involves using denture-cleaning solutions. Sodium hypochlorite is commonly used but can damage acrylic resin. An alternative is using natural ingredients, such as P. canescens jack, known for its antibacterial properties. Objective: This study evaluated the antibacterial effects of different P. canescens jack extract fractionation against Staphylococcus aureus on hot-polymerized acrylic resin. Methods: Extracts were fractionated using ethanol, ethyl acetate, and n-Hexane solvents. Acrylic resin plates (10x10x1 mm) were hot-polymerized and contaminated with Staphylococcus aureus, with 25 samples divided into five treatment groups: ethanol, ethyl acetate, n-Hexane, and a control group. The antibacterial activity was tested using a spectrophotometer and analyzed with One-way ANOVA and LSD tests to identify significant differences. Results: The study found a significant effect of P. canescens jack extract fractionation (p 0.05) across different solvents. The n-Hexane solvent at 1% concentration exhibited the highest growth inhibition, with a value of 0.015 nm, compared to other solvents. Conclusion: Fractionation of P. canescens jack extract using n-Hexane as a solvent showed superior antibacterial activity against Staphylococcus aureus compared to sodium hypochlorite, making it a better option for preventing denture stomatitis